Understanding the Mechanical Forces on the Sacrum Can Help Optimize Flap-based Pilonidal Sinus Reconstruction - Shintaro Kaneyuku, MD; Teruyuki Dohi, MD, PhD; Diya′ S. Hammoudeh, MD; Shigeyoshi Eura, MD, PhD; Yuta Kurokawa, MD; Rei Ogawa, MD, PhD, FACS (Plastic and Reconstructive Surgery, Global Open, 2024)
Background:. Pilonidal sinus can be treated with excision and flap reconstruction, but treatment is often complicated by wound dehiscence, infection, and recurrence. Understanding the mechanical forces on the sacrococcygeal area during posture change could help guide optimal flap choice. Methods:. Sixteen volunteers underwent measurements of skin-stretching, pressure, and shear stress on the sacrum when sitting relative to standing. Skin-stretching was measured by drawing a 4 × 4 cm square on the sacrum and measuring the vertical, horizontal, and diagonal axes. Pressure and shear stress was measured at six sacral points with a device. The data analysis highlighted the potential of the superior gluteal artery perforator (SGAP) flap for dissipating mechanical forces. Ten pilonidal sinus cases treated with SGAP flaps were retrospectively reviewed for 6-month outcomes. Results:. Sitting is associated with high stretching tension in the horizontal direction [estimated marginal mean (95% confidence intervals) = 17.3% (15.4%–22.6%)]. The lower sacrum experienced the highest pressure [106.6 (96.6–116.5) mm Hg] and shear stress [11.6 (9.7–13.5) N] during sitting. The transposed SGAP flap was deemed to be optimal for releasing the horizontal tension and providing sufficient subcutaneous tissue for ameliorating pressure/shear stress during sitting. It also has high blood flow and can therefore be used with large lesions. Moreover, its donor site is above the high-pressure/stress lower sacrum. Retrospective analysis showed that no patients experienced complications. Conclusions:. Sitting is associated with high mechanical forces on the sacrococcygeal skin. The transposed SGAP flap may ameliorate these forces and thereby reduce the risk of complications of pilonidal sinus reconstruction for large defects.